Pengaruh Iklan dan Program Gratis Ongkir terhadap Keputusan Pembelian pada Marketplace Tiktok Shop d Kota Bima - Fajriatin, Putri; Muhajirin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study was conducted to determine the effect of advertising and the free shipping program on purchasing decisions at the Tiktok Shop marketplace in Bima City by taking the type of associative research. Likert scale questionnaire as a research instrument. The population used in this study were all consumers who had shopped at an unknown Tiktok shop (Unknown Population). To determine the number of samples in an unknown population, the Cochran formula was used and a sample of 96 people was obtained. The sampling technique was carried out by purposive sampling method. Data collection techniques using observation, questionnaires and literature study. The research hypothesis is answered by t-test and f-test. The results of the study show that advertising and the free shipping program have a significant effect on purchasing decisions on the Tiktok Shop marketplace in Bima City.